Effect of exercise on plasma paraoxonase1 activity in rugby players: Dependance on training experience. (1st May 2013) - Otocka-Kmiecik, A.; Bortnik, K.; Szkudlarek, U.; Nowak, D.; Orłowska-Majdak, M.
<x xml:space="preserve">Abstract</x> Objectives: There are conflicting data on the influence of physical activity on paraoxonase1 (PON1) activity. The purpose of this study is to investigate the effect of maximal exercise (ME) on plasma paraoxonase (PON) and arylesterase (ARE) activity in elite rugby players. In addition, the influence of training experience and PON1 Q192R polymorphism on PON1 activity changes at ME was evaluated. Methods: Twenty-five elite rugby players ages 22.0 ± 3.71 years, consisting of 11 juniors - J (2-7 years of training) and 14 seniors - S (8-15 years of training), completed ME on a cycle ergometer. PON and ARE activity, ferric reducing activity of plasma (FRAP), uric acid (UA), and total bilirubin concentration, as well as thiobarbituric acid reactive substances and lipid profile were investigated in the plasma before, at the bout, and 30 minutes after ME. Results: At the bout of ME we found an increase in PON1 activities, ARE/high-density lipoprotein C ratio, TBil, and TChol. However, ARE activity changes were not observed in the group of rugby players training for ≤7 years. FRAP and UA increased later - 30 minutes after ME. Conclusion: We conclude that in rugby players PON1 changes during ME depend on age, body composition, and training experience. The influence of PON1 Q192R polymorphism on PON1 changes at ME remains debatable.